RETURN-TO-PLAY FOLLOWING INJURY: WHOSE DECISION SHOULD IT BE?. Issue 7 (11th March 2014) - Shrier, I; Safai, P; Charland, L
Abstract : Background: Return-to-play (RTP) decision-making is required for every injured athlete. However, conflict can and often does emerge between sport medicine clinicians, athletes, coaches and sport associations when engaging in recommended shared decision making processes. Objective: This study explores differences in professionals' opinion about which criteria should be used for RTP decisions, and who is best able to evaluate them. Design: Cross-sectional survey. Setting: Canada. Participants: Canadian sport medicine physicians, physiotherapists, athletic therapists, chiropractors, massage therapists, athletes, coaches and representatives from the Canadian Olympic Committee, Canada Games, and Canadian Soccer Association. Risk factor assessment: None. Main outcome measurements: Descriptive analysis of a 10-min online survey that asked respondents to rate criteria as mandatory to irrelevant on a 5-point Likert scale, and to indicate which profession was best able to evaluate the criteria. Results: In general, medical doctors, physiotherapists and athletic therapists were considered best able to assess factors related to risk of injury and complications from injury. Each clinician group (except sport massage therapists) generally believed their own profession has the best capacity to evaluate the criteria. Athletes, coaches and sport associations were considered to have the best capacity to assess factors related to competition (desire, psychological and financial impact, and loss of competitive standing). There remained considerable heterogeneity both between and within stakeholder groups. Conclusions: We found that differences in approach to RTP decisions were generally greater within stakeholder groups compared to between stakeholder groups. If shared decision making is to become the norm in clinical sport medicine, we will need to begin a more fulsome discussion on which discrepancies can be addressed by education and research, and which simply reflect the divergence of values among different individuals.